Sociodemographic and lifestyle factors and the risk of metabolic syndrome in taxi drivers: A focus on street food - Sekgala, Machoene Derrick; Opperman, Maretha; Mpahleni, Buhle; Mchiza, Zandile June-Rose (Frontiers in Nutrition, 2023)
This study therefore aimed to investigate the sociodemographic and lifestyle factors that predispose South African minibus taxi drivers who operate around the Cape Town Metropole area to the risk of developing MetS. This was a cross-sectional study that included 185, 20 years and older male minibus taxi drivers, ages 20 and older, who were interviewed about their socio-demographic characteristics and lifestyle factors using a previously validated questionnaire. They also underwent physical and metabolic assessments, and the International Diabetes Federation (IDF) criteria were used to diagnose those who had MetS. Overall, the mean age and driving experience of the taxi drivers were 40.0 years (SD: 10.7) and 9.1 years (SD: 7.4), respectively, with those presenting with MetS being significantly older and had more driving experience than those without MetS. Older participants and those who had driving experience of 8 years and more, were 3 and 2.9 times more likely to present with MetS compared to those who were younger and had 7 years or less of driving experience. Most of the taxi drivers (70%) met the IDF diagnostic criteria for MetS. Smokers, those who spent 100 ZAR (5.90 USD) or more and those who expended less than 1.4 MET-minute/week were 1.96, 2.0 and 13.6 times more likely to present with MetS compared to their counterparts who did not smoke, those who spent less than 100 ZAR, and those who expended 1.4 or more MET-minute/week. Alcohol and sugar sweetened beverages (SSBs) consumption, as well as the consumption of takeaway and fried foods, snacks and crisps sold by the street food (SF) vendors increased the likelihood of MetS, abnormal HDL-C, TG and hypertension, while avoiding take-away and fried foods decreased this likelihood. Those taxi drivers who also avoided consuming fresh fruits presented with abnormal HDL-C, while those who consumed canned fish daily and 1 to 3 times a week had reduced the likelihood of MetS and TG. These outcomes have a public health implication that calls for South African policy makers to endorse system-level approaches where taxi drivers’ lifestyle changes are motivated within the taxi industry to improve their health risk profile.